Cierpiący mesjasz w starotestamentalnych przepowiedniach prorockich - Homerski, Józef (The Biblical Annals, 2017)
The author conducts an exegetical and theological analysis of the texts of Is 50,4-9; 52,13-53,12; Zc 12,10 and 13,7, and Ps. 22,2-22. In this analysis he wants to answer three questions: what kind of person is the Messiah as described in the texts analysed: what does the salutary function of the protagonist of those prophecies consist in: and is there any influence of those Old Testament texts on the descriptions of Christ’s passion in the gospels. The exegesis of the mentioned texts allows the author to state, that God’s Servant, the Messiah, will be a teacher and a charismatist, but his proper mission will consist in subjecting himself to the will of the redeeming God who through His Servant’s poverty, suffering, loneliness and death as well as through the humiliation even after death, is going to redeem all the mankind. Hence the essence of the Servant’s salutary function consists in physical and moral suffering and in giving his life as a propitiatory sacrifice for human sins. The Servant will accept his mission voluntarily. Being the oblation, he will at the same time have the function of an advocate. And God will accept his sacrifice, forgiving the sin and excusing those who are guity. Old Testament quotations in the gospels show that the evangelists knew the Old Testament prophecies and they referred some of them directly to Christ, but it cannot be stated, that those prophecies had some distinct influence on the formulation of the descriptions of Christ’s passion.